Synthesis and Antimicrobial Activity of 3,5-Diarylpyrazoles - Rajendra Prasad, Y.; Lakshmi Prasanna, G.; Chakradhar, V. (Asian Journal of Chemistry, 2016)
3,5-Diarylpyrazoles having substituents on the aryl group were synthesized from diaryl-b-diketones by reaction with hydrazine hydrate and characterized by spectral studies. All the four synthesized compounds synthesized have been tested for their antimicrobial activity.